Water risk assessment in supply chains. (20th January 2019) - Schaefer, Torben; Udenio, Maximiliano; Quinn, Shannon; Fransoo, Jan C.
Abstract: Sustainability has long been recognized as a fundamental practice in manufacturing. In recent years, firms have been devoting resources to reduce their carbon footprint, greenhouse gas emissions, and water use. However, the problem of measuring and acting upon water risk in the supply chain has not yet been tackled in the literature. Unlike other environmental concerns, water risk is a local phenomenon that needs to be quantified at the catchment level. Thus, the impact of a production process cannot be location-agnostic and must be analyzed within its particular context—ideally at the production site level. Furthermore, recent trends in manufacturing (such as "local production") are expected to put increased pressure in areas where regulations are lax and water risk is high (e.g., India, China). Such considerations should be taken into account within the context of supplier management processes. We introduce a hierarchical framework, using Monte Carlo Analytic Hierarchy Process (MCAHP), to aggregate relevant indicators into an index score designed to assess suppliers' water risk based on their location. Our framework distinguishes between strategic sourcing decisions and tactical supplier management. Thus, it supports two applications of particular importance for managers: the top down identification of regional-level water-risk and variability, and the bottom up supplier management at a raw-material level. We illustrate the application of our framework with a case study conducted within a business unit of Procter & Gamble (P&G), the global consumer products company; examining 1066 direct suppliers in over 75 countries. Our strategic sourcing analysis identifies 340 suppliers with high water-risk and singles out 3 countries in critical condition; experiencing high water-risk in addition to precarious conditions for civilian access to water. Additionally, our bottom up analysis identifies a single supplier of a water-intensive raw material that is expected to become critical in the coming years; thus enabling targeted supplier management from a water-stewardship perspective.